PERANCANGAN LABORATORIUM DENGAN MENGGUNAKAN BNA BLEND 75:25:10R PADA CAMPURAN SPLIT MASTIC ASPHALT - , ayu kusuma halim; , Dr. Ir. Latif Budi Suparma, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Recently the increase in traffic growth causes premature damage to pavement, then the need for an innovation to overcome these problems, one of which is by using modified asphalt. Modified asphalt used in this study research is a blend of asphalt BNA 75:25:10R uses a mixture Split Mastic Asphalt (SMA), which is a mixture of high school that has a mix of good characteristics for dense traffic and have high stability. Expected in this study Asphalt blend BNA 75:25:10 R can have the characteristics of a good asphalt material that can replace conventional asphalt. The study research was conducted by making specimen mix Split Mastic Asphalt (SMA) using BNA Blend 75:25:10R Asphalt and Pertamina Asphalt penetration 60/70 as asphalt control, with variations on the same asphalt content of each type of asphalt, as much as 6 levels of variation asphalt is 6%, 6.5%, 7%, 7.5% and 8%. Testing was done by Marshall standard, Marshall Immersion Test and Indirect tensile strength test (ITS). Optimum bitumen content of asphalt mixtures SMA with BNA Blend 75:25:10R is 7.6% while for asphalt pertamina penetration 60/70 is 7%. The use of asphalt BNA Blend 75:25:10R at SMA mixture causes the value of density, VMA, VFWA, IKS, stability and MQ are higher than pertamina asphalt AC 60/70, while for VITM and flow are lower than asphalt pertamina AC 60/70. And the value of the resulting Tensile Strength Ratio (TSR) BNA Blend 75:25:10R asphalt is 83.8397% lower than asphalt pertamina AC 60/70 that is 86.1347%.